2022
DOI: 10.3390/min12030304
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Halloysite/Ag2O Nanomaterials and Their Performance for Iodide Adsorption

Abstract: Halloysite/Ag2O (Hal/Ag2O) nanomaterials were prepared by growing Ag2O nanoparticles on the surface of nanotubular halloysite using silver nitrate solution under alkaline conditions. The nanomaterials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and N2 adsorption. Good dispersion of Ag2O nanoparticles with average sizes of 6.07 ± 2.5 nm and 8.04 ± 3.8 nm was achieved in the nanomaterials when using different concentrations of alkali. The nanomaterial with 6.36% Ag2O (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(54 reference statements)
0
7
1
Order By: Relevance
“…For the sample 12.5-Ag 2 O@MCM-41, an appreciable number of Ag 2 O nanoparticles could be found at the surface of MCM-41 ( Figure 2 d). Although the size of the Ag 2 O nanoparticles increased with its amount, it seemed that the size of Ag 2 O was smaller than that of the composites in which Ag 2 O nanoparticles were only at the surface of the supports [ 6 , 16 ]. For example, in the reported nanofibrillated chitin/Ag 2 O aerogels, the size of Ag 2 O could easily reach a diameter of more than 15 nm [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sample 12.5-Ag 2 O@MCM-41, an appreciable number of Ag 2 O nanoparticles could be found at the surface of MCM-41 ( Figure 2 d). Although the size of the Ag 2 O nanoparticles increased with its amount, it seemed that the size of Ag 2 O was smaller than that of the composites in which Ag 2 O nanoparticles were only at the surface of the supports [ 6 , 16 ]. For example, in the reported nanofibrillated chitin/Ag 2 O aerogels, the size of Ag 2 O could easily reach a diameter of more than 15 nm [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PSD curve of MCM-41 revealed that the pore size of its mesoporous channel was 3.8 nm ( Figure 3 b). The BET-specific surface area of MCM-41 was 951.0 m 2 /g, which is significantly larger than that of other carriers used to prepare Ag 2 O-based nanocomposites (such as TiO 2 spheres [ 7 ], chitin nanofibers [ 6 ], titanate nanolamina [ 15 ], and halloysite nanotubes [ 16 ]). The total pore volume of MCM-41 was 0.7568 cm 3 /g ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption is widely used in water purification in combination with other technologies, such as flocculation, coagulation, biological oxidation, sedimentation, oxidation/degradation processes and membrane processes [ 15 , 16 , 17 , 18 ]. Porous materials, including carbons, have been extensively used in water treatment [ 19 , 20 , 21 , 22 ]. For instance, zeolites which are very common materials used for water purification, are not suitable for the removal of iodide without modification as they are cation exchangers.…”
Section: Introductionmentioning
confidence: 99%